Longitudinal monitoring of cell-free DNA methylation in ALK-positive non-small cell lung cancer patients - Janke, Florian; Angeles, Arlou Kristina J.; Riediger, Anja Lisa; Bauer, Simone; Reck, Martin; Stenzinger, Albrecht; Schneider, Marc; Muley, Thomas; Thomas, Michael; Christopoulos, Petros; Sültmann, Holger (Clinical epigenetics, 2022)
DNA methylation (5-mC) signals in cell-free DNA (cfDNA) of cancer patients represent promising biomarkers for minimally invasive tumor detection. The high abundance of cancer-associated 5-mC alterations permits parallel and highly sensitive assessment of multiple 5-mC biomarkers. Here, we performed genome-wide 5-mC profiling in the plasma of metastatic ALK-rearranged non-small cell lung cancer (NSCLC) patients receiving tyrosine kinase inhibitor therapy. We established a strategy to identify ALK-specific 5-mC changes from cfDNA and demonstrated the suitability of the identified markers for cancer detection, prognosis, and therapy monitoring.
Gesehen am 16.11.2023